La matérialité décadente et l’économie: entre la fascination et la ruse - Sicotte, Geneviève (Nordlit, 2012)
Decadent literature is characterized by numerous descriptions of material luxury, whether in decoration, clothing and trinkets. This treatment of materiality has generally been interpreted by critics as a literary refusal of the bourgeois world, which was seen to be obsessed with productive work. But the evolution of the bourgeoisie in the last decades of the 19th century leads to new types of consumption precisely based on the useless and the unnecessary. It must then be understood that the literary representation of luxury is in part influenced by the behavior of the rising haute bourgeoisie of the time. Therefore, the decadent materialism could be seen not as a transgressive figure, but as a figure of disengagement, strongly influenced by the social codes of its time. However, in the most interesting literary texts, the representation of beautiful objects is problematized, marked by negativity, the gift and the play on the decorative status of the text. This representation sets up the terms of a real economic counter-discourse.